2017
DOI: 10.1089/cmb.2016.0173
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila H2A and H2A.Z Nucleosome Sequences Reveal Different Nucleosome Positioning Sequence Patterns

Abstract: Nucleosomes are implicated in transcriptional regulation as well as in packing and stabilizing the DNA. Nucleosome positions affect the transcription by impeding or facilitating the binding of transcription factors. The DNA sequence, especially the periodic occurrences of dinucleotides, is a major factor that affects the nucleosome positioning. We analyzed the Drosophila DNA sequences bound by H2A and H2A.Z nucleosomes. Periodic patterns of dinucleotides (weak-weak/strong-strong or purine-purine/pyrimidine-pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…nucleosome maps are noticeably different by the absence of periodically positioned and 32 phased nucleosomal arrays in the in vivo maps where an ATP-dependent chromatin 33 re-modeler is responsible for the well-spaced nucleosome array [18]. In addition to the 34 sequence composition there are other factors in vivo such as post-translational 35 modifications (PTM) of histone tails, transcription factor binding and remodeling 36 complexes that influence positioning of nucleosomes and in turn tune chromatin 37 accessibility and gene expression [5,18]. 38 It was shown that nucleosome remodeling takes place in response to stress and alters 39 a gene expression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…nucleosome maps are noticeably different by the absence of periodically positioned and 32 phased nucleosomal arrays in the in vivo maps where an ATP-dependent chromatin 33 re-modeler is responsible for the well-spaced nucleosome array [18]. In addition to the 34 sequence composition there are other factors in vivo such as post-translational 35 modifications (PTM) of histone tails, transcription factor binding and remodeling 36 complexes that influence positioning of nucleosomes and in turn tune chromatin 37 accessibility and gene expression [5,18]. 38 It was shown that nucleosome remodeling takes place in response to stress and alters 39 a gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…nucleosomes are characterized by a periodical 10 base pairs AA/TT 182 dinucleotide frequency distributions most clearly manifesting in yeast. At various 183extents it is seen also in other model organisms -human, mouse, worm[35] and fruit 184 fly[36].We investigated patterns formed by WW/SS and RR/YY pairs of dinucleotides 185 and individual AA/TT/TA and CC/GG dinucleotides which carry nucleosome 186 positioning signals by their periodical arrangements. Frequency analysis (Fourier 187 transform) of dinucleotide profiles in mouse brain NAC showed peaks at 10.1-10.4 base 188 period in agreement with the anticipated 10bp periodicity.…”
mentioning
confidence: 99%